2014
DOI: 10.4238/2014.february.28.5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations of ISL1 associated with human congenital heart disease in Chinese Han people

Abstract: ABSTRACT. Congenital heart disease (CHD) is the most common birth abnormality, but the etiology of CHD is unknown. ISL1 may play a fundamental role in cardiac morphogenesis, and mutations of this gene could cause CHD. To evaluate whether genetic variations of ISL1 are associated with CHD in Chinese Han people, polymerase chain reaction restriction fragment-length polymorphism and SNaPshot were used to examine 9 polymorphisms of ISL1 in 233 patients with CHD as well as 288 healthy controls. We found that one SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…121) Previous studies demonstrated that several common polymorphisms in the ISL1 gene conferred an enhanced susceptibility to CHDs. 114,115) Stevens and coworkers 114) performed a case-control study of the 30 polymorphisms located at the ISL1 locus in 300 pediatric cases affected with complex CHDs and 2,201 healthy control children and found that 8 polymorphisms (rs6449612, rs6449600, rs4865656, rs2115322, IVS1+17C>T, rs6869844, rs1017, rs6867206) in and near ISL1 were significantly associated with enhanced vulnerability to CHDs. In order to independently verify the above-mentioned results, they made a replication research of these genetic polymorphisms in 1,044 new patients and 3,934 independent control individuals and validated the significant association of these polymorphisms with increased susceptibility to nonsyndromic CHDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…121) Previous studies demonstrated that several common polymorphisms in the ISL1 gene conferred an enhanced susceptibility to CHDs. 114,115) Stevens and coworkers 114) performed a case-control study of the 30 polymorphisms located at the ISL1 locus in 300 pediatric cases affected with complex CHDs and 2,201 healthy control children and found that 8 polymorphisms (rs6449612, rs6449600, rs4865656, rs2115322, IVS1+17C>T, rs6869844, rs1017, rs6867206) in and near ISL1 were significantly associated with enhanced vulnerability to CHDs. In order to independently verify the above-mentioned results, they made a replication research of these genetic polymorphisms in 1,044 new patients and 3,934 independent control individuals and validated the significant association of these polymorphisms with increased susceptibility to nonsyndromic CHDs.…”
Section: Discussionmentioning
confidence: 99%
“…110) In humans, multiple variants in ISL1 have been reported to confer an enhanced vulnerability to CHDs in diverse cohorts of patients. [114][115][116] These results make it justifiable to scan ISL1 for mutations underlying CHDs in another cohort of patients.…”
mentioning
confidence: 96%
“…In addition, we found that both phenotypes are not linked, and that the cardiac phenotype is associated with a novel mutation in the gene encoding CSRP1. This is the second gene encoding a LIM protein shown to be implicated in CHD after ISL1 (Stevens et al, 2010 ; Luo et al, 2014 ). In addition, we interrogated the penetrance of this mutation by searching for potential modifiers.…”
Section: Discussionmentioning
confidence: 99%
“…ISL1 rs1017 is one of the most frequently reported ISL1 variants; however, its correlation with CHD remains controversial. ISL1 rs1017 was reported to be related to the risk of CHD in a white population (Stevens et al, 2010) and a Chinese cohort (Luo et al, 2014), while the other studies showed opposite results (Xue et al, 2012;Cresci et al, 2013). Moreover, ISL1 haploinsufficiency was shown to be associated with d-transposition of the great arteries (d-TGA) (Osoegawa et al, 2014).…”
Section: Islet1 and Congenital Heart Diseasesmentioning
confidence: 99%